2018
DOI: 10.1186/s13550-018-0387-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on radiopharmaceutical DOTA-minigastrin analogue (CP04) complexes and their interaction with CCK2 receptor

Abstract: BackgroundThe cholecystokinin receptor subtype 2 (CCK-2R) is an important target for diagnostic imaging and targeted radionuclide therapy (TRNT) due to its overexpression in certain cancers (e.g., medullary thyroid carcinoma (MTC)), thus matching with a theranostic principle. Several peptide conjugates suitable for the TRNT of MTC have been synthesized, including a very promising minigastrin analogue DOTA-(DGlu)6-Ala-Tyr-Gly-Trp-Met-Asp-Phe-NH2 (CP04). In this contribution, we wanted to see whether CP04 bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…The assignment was carried out with routine correlation spectroscopy (COSY), rotating frame nuclear Overhauser effect spectroscopy (ROESY), heteronuclear single quantum correlation (HSQC), and heteronuclear multiple bond correlation (HMBC) spectra, and the rotating-frame Overhauser effect (ROE) intensities were converted into distance restraints. Structure calculations using these restraints were performed with the XPLOR-NIH software package , and confirmed random coil conformations in all cases. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assignment was carried out with routine correlation spectroscopy (COSY), rotating frame nuclear Overhauser effect spectroscopy (ROESY), heteronuclear single quantum correlation (HSQC), and heteronuclear multiple bond correlation (HMBC) spectra, and the rotating-frame Overhauser effect (ROE) intensities were converted into distance restraints. Structure calculations using these restraints were performed with the XPLOR-NIH software package , and confirmed random coil conformations in all cases. , …”
Section: Resultsmentioning
confidence: 99%
“…Despite great recent advances in the structural determination of GPCRs, the three-dimensional structure of the CCK2R and the precise binding mode of cholecystokinin, gastrin, and related peptides to this receptor are not yet known. However, several mutagenesis and modeling studies have identified essential regions and residues for ligand binding. ,, To get a better understanding of the properties of TZMG 6 , we built a computational model of this ligand bound to the CCK2R (Figure A and SI, p S90). The C-terminal part of the peptide (Trp 14 -Nle 15 -Asp 16 -Phe 17 -NH 2 ) forms a short turn buried in the orthosteric binding site (Figure B), where it can interact with, e.g., residues Arg 57 , His 376 , His 207 , and Arg 356 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This improved stability against enzymatic degradation in vivo was not an unexpected finding. Methylation of the peptide bond between Trp and Nle and introduction of voluminous amino acids at the C terminus were already investigated for CCK4 analogs, achieving compounds that are protected from degradation in rat brain homogenates (23). Higher bioavailability is likely to increment the amount of intact radiopeptide reaching the target site.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, the imaging portion of a radiopharmaceutical is positioned far from the binding site so as not to have a negative affect on the binding affinity. [54][55][56][57][58] This is particularly common for radiotracers bearing metal chelators due to the relatively large size of the appended metal-complex. However, the authors chose to apply a more compact design that incorporates the imaging moiety in a position crucial for binding.…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%